1998
DOI: 10.1007/s004240050663
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the carbachol-activated nonselective cationic current by antibody against alpha subunit of G o protein in guinea-pig gastric myocytes

Abstract: In this study, we investigated which subtype of GTP-binding protein (G protein) is related to muscarinic activation of nonselective cation (NSC) channels in gastric smooth muscle. Inward cationic current was activated by the application of 50 microM carbachol (ICCh) at a holding potential of -60 mV with the same CsCl-rich solution in both pipette and bath. The same cationic current as ICCh was slowly activated by the dialysis of guanosine 5'-O-(3-thiotriphosphate) (GTP[gamma-S]) through the pipette. Since it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 7 publications
2
36
0
Order By: Relevance
“…However, a similar result was obtained in guinea-pig gastric myocytes where antibodies against Ga o were effective in blocking the muscarinic cation current (Kim et al, 1998).…”
Section: Discussionsupporting
confidence: 72%
“…However, a similar result was obtained in guinea-pig gastric myocytes where antibodies against Ga o were effective in blocking the muscarinic cation current (Kim et al, 1998).…”
Section: Discussionsupporting
confidence: 72%
“…Thirdly, its activation depends on G-protein activity (8,9). We also showed that the Go type among GTP-binding proteins is responsible for activating the channel (10). Fourthly, the unitary conductance was about 25 -30 pS (1 -3).…”
mentioning
confidence: 88%
“…In these cell types, the I cat response is abolished by pertussis toxin (PTX) which selectively uncouples G i / G o proteins from the associated receptors (2, 7 -10). With the use of antibodies, the G protein involved in the signal transduction was identified as G o protein (11,12). Based on these results and the general thought that M2 receptors preferencially couple PTX-sensitive G proteins (8), the M2 subtype is supposed to mediate cationic channel opening through G o proteins.…”
Section: Introductionmentioning
confidence: 98%